Oxidative Stress Function in Women over 40 Years of Age, Considering Their Lifestyle - Gonçalves Mota, Maria Paula; Santos, Zirlene; Soares, Jorge; Pereira, Ana; Fonseca, Sandra; Peixoto, Francisco; Gaivão, Isabel; Oliveira, Maria (Frontiers in Endocrinology, 2017)
Aging is dependent on biological processes that determine the aging of the organism at the cellular level. The Oxidative Stress Theory of Aging might explain some of the age-related changes in cell macromolecules. Moreover, exposome and lifestyle may also induce changes in cell damage induced by oxidative stress. The aim of the present study was to analyze the related redox changes in lymphocyte function of healthy women over 40 years old. Three groups: young (YG: 40-49 years), middle-aged (MAG: 50-59 years) and older (OG: ≥60 years) were evaluated on anthropometric variables, blood pressure, cardiovascular fitness, lifestyle habits, perceived stress, DNA damage, malondialdehyde, catalase activity and total antioxidant capacity. Physical activity and cardiovascular fitness were significantly higher in YG and MAG as compared to the OG. Systolic blood pressure increased significantly with group age. Frequency and total amount of alcohol intake were lower in the OG and higher in the MAG. No significant differences were observed between the three groups in oxidative stress parameters. Only alcohol consumption was associated with the higher DNA FPG-sensitive sites, and only in the YG (p<0.05). Healthy lifestyle is critical to avoiding major ailments associated with aging. This may be inferred from the lack of significant differences in the various oxidative stress parameters measured in the healthy women over the age of 40 who took part in the study. Conscious lifestyle behaviors (decrease in alcohol and smoking habits) could have impaired the expected age-related oxidative stress increase.